A Prospective, Split-Face, Randomized, Double-Blind Study Comparing OnabotulinumtoxinA to IncobotulinumtoxinA for Upper Face Wrinkles. Issue 5 (May 2015) - Yeilding, Ruth Hill; Fezza, John P.
Abstract : Background: The authors sought to compare the newest U.S. Food and Drug Administration–approved botulinum toxin type A product, incobotulinumtoxinA, to onabotulinumtoxinA for upper face wrinkles. This is the first prospective, split-face, randomized, double-blind study addressing three types of facial wrinkles using a 1:1 dose ratio. Methods: The study was designed, institutional review board approval was obtained, and 45 patients were enrolled. A three-judge independent reviewer panel compared photographs of patients to the upper face validated assessment scales, selecting a grade ranging from 0 (no lines) to 4 (very severe) for the degree of glabellar lines, crow's feet, and forehead lines for each side of the face for photographs taken before treatment and 3 days, 2 weeks, 3 months, and 4 months after treatment. For toxin comparison, the difference in the magnitude of the degree of wrinkle scale at each period compared to before treatment was calculated and statistical analysis performed. Individual wrinkle types and all three wrinkle types combined were analyzed. Results: Both products offered significant reduction in individual and combined wrinkles at comparable time points; however, onabotulinumtoxinA had significantly greater combined dynamic wrinkle reduction at 3 days ( p < 0.010), 2 weeks ( p < 0.008), 3 months ( p < 0.013), and 4 months ( p < 0.045). Conclusions: For identical dosage, both onabotulinumtoxinA and incobotulinumtoxinA are safe and effective in reducing dynamic wrinkles in the upper face; however, for the authors' dosages, onabotulinumtoxinA had statistically greater efficacy at 3 days, 2 weeks, 3 months, and 4 months. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.